THE EXISTENCE OF THE PRINCIPLE OF CONTRACTUAL FREEDOM IN STANDARD CONTRACT OF THE EMPLOYMENT AGREEMENT - , Aan Muhsinin; , Dr. Ari Hernawan, S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to determine the existence of the principle of contractual freedom in standard contract on the employment agreement and legal protection for the worker and employer equally. This study is a normative legal research that discusses a principle applied in the Contract Law which is the principle of contractual freedom. Source of data used is secondary data. The data is collected through document study or library reseacrh. The data is analyzed qualitatively and the results are presented descriptively. The results show that the existence of the principle of contractual freedom in standard contract on the employment agreement is a principle which implies that every person is free to make the employment agreement, to make the employment agreement with anyone, to determine the content, to determine the form and to determine the choice of law with the limitations that the agreement must fulfill requirements, must not contain the prohibited cause, must not contrary to propriety, customs and laws and must be conducted in good faith which supported by the governmentâs intervention by making the manpower laws to achieve common justice. Meanwhile, the legal protection for the workers and the employer equally can be known from the example of the employment agreement on one company. That employment agreement shows already provide the legal protection equally even if there is exoneration clauses made in standard by the employer because, however, the employer has a higher position than the workers. The employer is more dominant to determine the contents of the agreement. This is a form of the legal protection for the employer that is intended to support the smooth operation of the company and to increase the workers productivity